PRINCIPLES OF ISLAMIC LAW IN ACTIVITIES ENDORSEMENT FOR MUSLIM FEMALE INFLUENCERS: STUDY BASED ON TAFSIR AL-QUR'AN - Susanti, Desi; Ismail, Hidayatullah; al Sarireh, Amer Jamil Abduh; Hadi, Henrizal; Abrar, Ahyarul; Hanifah, Syifa (Hukum Islam, 2024)
In the increasingly developing digital era, endorsements have become a popular marketing strategy on social media. However, for a Muslim woman who becomes an influencer, this activity must be by Sharia values, which include honesty, transparency, and moral responsibility. This study aims to analyze the application of Islamic legal principles in endorsement activities by Muslim influencers. The research method is descriptive and qualitative, with data obtained through observation and literature studies. The results of the research show that all muamalah can be done unless there are arguments that prohibit it. Therefore, Muslim influencers must comply with Sharia principles, which include product halalness, clarity of status in transactions, price compliance with quality, and honesty in conveying information. The novelty of this research lies in the deep integration of Islamic legal principles with digital endorsement. This study extends the discourse of Islamic law into the context of modern marketing. It offers applicable ethical guidance for Muslim influencers in the digital era by introducing the perspective of maqashid Sharia (the objectives of Sharia) in endorsement activities.